Efektivitas Pengelolaan Keuangan melalui Penerapan Good Governance pada Pondok Pesantren - Chysara, Daris Iqbal; Nugraha, Mulyawan Safwandy (Perkumpulan Peneliti dan Pegiat Literasi, 2024)
This research presents an in-depth analysis of financial management at Pondok Pesantren Nurul Mukmin Attaqwa Arjasari. Through data collection methods involving on-site observations, interviews, and documentation, the research provides a comprehensive overview of financial management at Pondok Pesantren Nurul Mukmin Attaqwa Arjasari. Furthermore, the study outlines specific numerical figures for components such as school operational expenses, teacher salaries and allowances, and reserve funds. The research results offer a deeper understanding of the financial management model in this educational institution and discuss potential improvements and developments for the future. Thus, this article contributes to enhancing the effectiveness of financial management in the context of Pondok Pesantren Nurul Mukmin Attaqwa Arjasari. This research indicate the primary source of funding for the Pondok Pesantren comes from donations and contributions from the community, as well as income from supplementary educational activities. There is a need to improve the budget planning process. While planning exists, more structured and clear policies need to be implemented to optimize fund utilization. Overall budget utilization has been efficient, but there is room for improving financial management in specific areas, such as enhancing the competence of human resources. These research findings provide a foundation for educational institutions to enhance their financial management model and plan more effective and sustainable future steps.